Aortic branch vessel flow during resuscitative endovascular balloon occlusion of the aorta. Issue 1 (January 2019) - Hoehn, Melanie R.; Teeter, William A.; Morrison, Jonathan J.; Gamble, William B.; Hu, Peter; Stein, Deborah M.; Brenner, Megan L.; Scalea, Thomas M.
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a torso hemorrhage control adjunct. Aortic branch vessel flow (BVF) during REBOA is poorly characterized and has implications for ischemia-reperfusion injury. The aim of this study is to quantify BVF in hypovolemic shock with and without REBOA. METHODS: Female swine (79–90 kg) underwent anesthesia, 40% controlled hemorrhage and sonographic flow monitoring of the carotid, hepatic, superior mesenteric, renal, and femoral arteries. Animals were randomized to REBOA (n = 5) or no-REBOA (n = 5) for 4 hours, followed by full resuscitation and balloon deflation for 1 hour. RESULTS: All animals were successfully induced into hemorrhagic shock with a mean decrease of flow in all vessels of 50% from baseline ( p < 0.001). Deployment of REBOA resulted in a 200% to 400% increase in carotid flow, but near complete abolition of BVF distal to the balloon. The no-REBOA group saw recovery of BVF to 100% of baseline in all measured vessels, except the hepatic at 50% to 75%. two-way analysis of variance confirmed a significant difference between the groups throughout the protocol ( p < 0.001). During resuscitation, the REBOA group saw BVF restore to between 25% and 50%, but never achieving baseline values. The lactate at 4 hours was significantly higher in the REBOA versus no-REBOA group (17.2 ± 0.1 vs. 4.9 ± 1.4; p < 0.001). CONCLUSION: REBOA not only abolishing BVF during occlusion, but appears to have a post-REBOA effect, reducing visceral perfusion. This may be a source of REBOA associated ischemia-reperfusion injury and warrants further investigation in order to mitigate this effect.